Generation of a control induced pluripotent stem cell line (CBRCULi014-A) derived from the lymphoblastoid cells of a pediatric individual - Thiéry De Serres-Bérard; Valérie Pouliot; Jack Puymirat; Mohamed Chahine (Stem Cell Research)
Lymphoblastoid cell lines serve as a readily and continuous resource for generating induced pluripotent stem cells (iPSCs), enabling the modeling of various genetic disorders in vitro. When investigating congenital and infantile diseases, age-matched controls derived from pediatric individuals are typically necessary, yet they may be scarce or difficult to obtain. Here, the Sendai virus system was employed to introduce reprogramming factors into lymphoblastoid cells derived from an apparently healthy 4-year-old female. The generated iPSCs strongly expressed pluripotency cell markers and displayed robust trilineage differentiation. CBRCULi014-A is therefore a reliable control iPSC line for pediatric disease investigation.